2013
DOI: 10.1111/ene.12248
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels correlate with benign paroxysmal positional vertigo

Abstract: Elevated SUA is positively correlated with BPPV, requiring further efforts to clarify the exact mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 38 publications
(52 reference statements)
9
32
0
Order By: Relevance
“…A case–control histopathological human temporal bone study found that the prevalence of cupular and free‐floating deposits in the lateral and posterior semicircular canals was significantly higher in individuals with type 1 diabetes mellitus than in the temporal bones of normal age‐matched controls . Another systemic link was described recently wherein lipid profiles and serum uric acid levels were found to be higher in individuals with BPPV than in controls . Other conditions that have been associated with BPPV include chronic thyroiditis, hypertension, hyperlipidemia, stroke, atherosclerosis, and osteoporosis.…”
Section: Etiological Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A case–control histopathological human temporal bone study found that the prevalence of cupular and free‐floating deposits in the lateral and posterior semicircular canals was significantly higher in individuals with type 1 diabetes mellitus than in the temporal bones of normal age‐matched controls . Another systemic link was described recently wherein lipid profiles and serum uric acid levels were found to be higher in individuals with BPPV than in controls . Other conditions that have been associated with BPPV include chronic thyroiditis, hypertension, hyperlipidemia, stroke, atherosclerosis, and osteoporosis.…”
Section: Etiological Factorsmentioning
confidence: 98%
“…30 Another systemic link was described recently wherein lipid profiles and serum uric acid levels were found to be higher in individuals with BPPV than in controls. 31 Other conditions that have been associated with BPPV include chronic thyroiditis, 32 hypertension, hyperlipidemia, stroke, 2 atherosclerosis, 33 and osteoporosis. To find a statistical link between common comorbidities affecting older adults (hypertension, diabetes mellitus, osteoarthrosis, osteoporosis, and depression) and recurrent episodes of BPPV, data from more than 1,000 individuals with BPPV in 11 centers in seven countries were examined in a recent study.…”
Section: Etiological Factorsmentioning
confidence: 99%
“…As we all know, age, gender, sex hormones, osteoporosis, hypertension, hyperlipidemia, diabetes and hyperuricemia are all considered as risk factors of BPPV (6)(7)(8)(9). According to previous study that cerebrovascular risk factors in uenced BPPV recurrence (10).…”
Section: Discussionmentioning
confidence: 99%
“…One study found patients with BPPV had higher serum uric acid levels than controls15: hyperuricaemia-associated crystal formation in the semicircular canals makes an attractive hypothesis, and although not universally reproduced16 is certainly a potential mechanism 17 18…”
Section: Pathophysiologymentioning
confidence: 99%